1985
DOI: 10.1002/macp.1985.021860208
|View full text |Cite
|
Sign up to set email alerts
|

Cinétiques de télomérisation, 1. Determination des lois applicables à la synthèse des télomères à DPn moyens en télomérisation radicalaire

Abstract: The kinetics of free radical telomerization was studied. The theoretical relations that can be applied in reactions of this type, were evaluated. When transfer predominates, the equations giving the variations of monomer, telogen and initiator as a function of time were established. Moreover, instantaneous and cumulated number and weight average degrees of polymerization were calculated. The resulting relations were checked on the example of the telomerization of 2,3-epoxypropyl methacrylate with bromotrichlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 13 publications
2
21
0
Order By: Relevance
“…The decrease of molar mass versus conversion is characteristic of a conventional radical telomerization reaction 33, 43. As previously demonstrated,44, 45 the evolution of the number‐average molar mass with monomer conversion, in the case of telomerization reaction, can be predicted by the following equation: where [M] 0 , M monomer [CTA] 0 , p , and C Tr stand for the initial monomer concentration, the molar mass of the monomer, the initial CTA concentration, the conversion, and the transfer constant of the CTA ( C Tr = k Tr / k p ), respectively.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…The decrease of molar mass versus conversion is characteristic of a conventional radical telomerization reaction 33, 43. As previously demonstrated,44, 45 the evolution of the number‐average molar mass with monomer conversion, in the case of telomerization reaction, can be predicted by the following equation: where [M] 0 , M monomer [CTA] 0 , p , and C Tr stand for the initial monomer concentration, the molar mass of the monomer, the initial CTA concentration, the conversion, and the transfer constant of the CTA ( C Tr = k Tr / k p ), respectively.…”
Section: Resultsmentioning
confidence: 73%
“…The decrease of molar mass versus conversion is characteristic of a conventional radical telomerization reaction. 33,43 As previously demonstrated, 44,45 the evolution of the numberaverage molar mass with monomer conversion, in the case of telomerization reaction, can be predicted by the following equation:…”
Section: Articlementioning
confidence: 91%
“…The polymerization is initiated either by radicals formed by the decomposition of the initiator 23) or by mercaptan radicals after a radical transfer reaction between a primary radical and a mercaptan 9,24) . The data shown here demonstrated that the formation of non-functional PHPMA-IBN chains depended on both the concentration of initiator and mercaptan, and suggested that there might be a competition of the two initiation mechanisms, depending on the reaction conditions (Scheme 1).…”
Section: Mechanistic Aspects Of the Polymerization In The Presence Ofmentioning
confidence: 99%
“…The relative amount of non-functional polymer chains (PHPMA-IBN) varied, as expected, with the molar ratios of mercaptan and AIBN to HPMA 22) . It is well known that different radicals may participate in the initiation reaction of the radical polymerization in the presence of mercaptans 9,[22][23][24] . It appears that to synthesize ST polymers with a high degree of functional- ity, a better understanding of the polymerization in the presence of mercaptans is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Because the SEC columns were calibrated with PS standards, a difference was found between the numberaverage molar masses obtained by NMR and SEC. The cumulative number-average molar masses (M n, th ) were calculated using the following equation: [15] DP n cum a R 0 1 À 1 À aC t 2…”
Section: Polymerization Of Styrene In Acetonitrile-water With 3 C As mentioning
confidence: 99%